Evaluasi Kinerja Terminal Arjosari Malang Dengan Metode IPA (Importance Performance Analisis) - Selan, Fitron Andrias ; Kristafi A, Andy; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Terminal Arjosari Raden Intan Road are located at no.1 Kecamatan Blimbing Malang. Terminal Arjosari planned to become a complete modern terminal in East Java which its status raised to the previous type A type B still. The purpose of this research is to know the performance of the service Terminal Arjosari Poor views from passenger satisfaction levels and further to figure out an alternative strategy that is appropriate for the performance of the terminal in order to optimally and passengers can be sated. Performance evaluation of variable analyzing Terminal security, maid service reliability/regularity of service, convenience, service convenience/affordability, equality service using the methods of NATURAL SCIENCE (Importance Performance Analysis). Site survey in the terminal. A survey of facilities and survey kuisoner to interview respondents (as many as 100 passengers).Of research results obtained by some facilities that do not yet exist in the terminal like information and health facilities, evacuation, fire extinguishers, the attendant checks the vehicle, light vehicle repair facilities, information on disorders travel by public transportation, nursing mothers, and ATM Center. From the results of the analysis with the method of IPA obtained 11 attributes according to the respondents is not satisfactory but their importance is very important. These results suggest that Terminal Arjosari Malang is not working optimally so that needed an alternative repair by optimizing service of 11 attributes by adding facilities that do not yet exist and to improve facilities that already exist but are not functioning optimally.